2019
DOI: 10.1002/anie.201910606
|View full text |Cite
|
Sign up to set email alerts
|

Bottom‐Up Assembly of DNA–Silica Nanocomposites into Micrometer‐Sized Hollow Spheres

Abstract: Although DNA nanotechnology has developed into a highly innovative and lively field of research at the interface between chemistry, materials science, and biotechnology, there is still a great need for methodological approaches for bridging the size regime of DNA nanostructures with that of micrometer‐ and millimeter‐sized units for practical applications. We report on novel hierarchically structured composite materials from silica nanoparticles and DNA polymers that can be obtained by self‐assembly through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…In the case of the DNA oligonucleotide‐modified SiNP‐4 , we observed that the fluorescence intensity is rapidly concentrated at the droplet boundary, leaving behind only negligible amounts of the fluorescent particles in the inner part of the droplet volume (Figure d, see also Figure S2). This observation suggests a strong electrostatic interaction between the negatively charged SiNP‐4 and the positively charged DOTAP shell, which is in agreement with earlier studies on the electrostatic formation of similar assemblies that employ DNA molecules …”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In the case of the DNA oligonucleotide‐modified SiNP‐4 , we observed that the fluorescence intensity is rapidly concentrated at the droplet boundary, leaving behind only negligible amounts of the fluorescent particles in the inner part of the droplet volume (Figure d, see also Figure S2). This observation suggests a strong electrostatic interaction between the negatively charged SiNP‐4 and the positively charged DOTAP shell, which is in agreement with earlier studies on the electrostatic formation of similar assemblies that employ DNA molecules …”
Section: Resultssupporting
confidence: 92%
“…Our results show that this process is mainly driven by electrostatic interaction; however, it is also evident that additional interactions occurring between the lipid layer at the droplet interface and particle‐bound surface groups, such as BSA moieties or DNA strands of different lengths, can have an influence on the segregation kinetics. Phase segregation processes of materials inside confined environments has been studied using polymers, nanocomposites, and bio‐functional moieties . However, to the best of our knowledge, no quantitative and systematic study of nanoparticle segregation inside microfluidic droplets has yet been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the cultivation of biofilms in microfluidic systems is making substantial progress 31 and this technological platform is also being used for research into supramolecular and dissipative material systems. [32][33][34] We therefore believe that future advancements of fluidically controllable DNA materials systems can make an important contribution to the development of novel biotechnological production systems.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, work on DNA-carbon nanotubes (CNT) composites shows that they have good biocompatibility 8,9 and DNA-quantum dot composites have been used as traceable and biocompatible nanomaterials for drug release. 10 Furthermore, DNA hydrogel composites containing silica nanoparticles (SiNP) have recently been used for the bottom-up assembly of hollow spherical microstructures 11 and SiNP/CNT-DNA composites were used as programmable and cell-instructive biocoatings. 12 While in the latter work the outstanding attractiveness of SiNP-DNA materials for cells was used for the adjustable adhesion of eukaryotic cells, previous work has already shown that DNA-functionalized SiNP are not only highly biocompatible but are also very efficiently ingested by cells.…”
Section: Introductionmentioning
confidence: 99%